2020
DOI: 10.7554/elife.57950
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in T cells from aged donors is maintained by spermidine and correlates with function and vaccine responses

Abstract: Vaccines are powerful tools to develop immune memory to infectious diseases and prevent excess mortality. In older adults, however vaccines are generally less efficacious and the molecular mechanisms that underpin this remain largely unknown. Autophagy, a process known to prevent aging, is critical for the maintenance of immune memory in mice. Here, we show that autophagy is specifically induced in vaccine-induced antigen-specific CD8+ T cells in healthy human volunteers. In addition, reduced IFNγ secretion by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 60 publications
(93 reference statements)
3
69
0
Order By: Relevance
“…This supports the notion that alterations of metabolic pathways in immune cells may directly cause inflammation-induced neurodegeneration. Importantly, there is a multitude of potential approaches to counteract ageassociated immune cell malfunctions by metabolic intervention, including supplementation of age-limited nutrients such as formate and glycine, and reinforcement of autophagy with spermidine (47,62). Of note, a recent study reported that mTOR inhibitor therapy in elderly humans decreased the incidence of infections, improved influenza vaccination responses and up-regulated antiviral immunity (68), thus highlighting the potential clinical relevance of such metabolic approaches in age-related immune dysfunctions.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the notion that alterations of metabolic pathways in immune cells may directly cause inflammation-induced neurodegeneration. Importantly, there is a multitude of potential approaches to counteract ageassociated immune cell malfunctions by metabolic intervention, including supplementation of age-limited nutrients such as formate and glycine, and reinforcement of autophagy with spermidine (47,62). Of note, a recent study reported that mTOR inhibitor therapy in elderly humans decreased the incidence of infections, improved influenza vaccination responses and up-regulated antiviral immunity (68), thus highlighting the potential clinical relevance of such metabolic approaches in age-related immune dysfunctions.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Recently, it was shown that spermidine modulates T cell differentiation towards a regulatory phenotype and dietary supplementation with spermidine reduced pathology in a mouse model of T cell transfer-induced colitis (61). Moreover, in a study in humans, spermidine supplementation was able to recover the autophagic flux and cellular functionality in T cells from old donors (62). Interestingly, spermidine was reported to reverse cellular senescence of B cells (63), an effect that has not yet been addressed in T cells.…”
Section: Metabolic Regulation Of T Cell Aging and Senescencementioning
confidence: 99%
“…By removing accumulated proteins and other unnecessary cytoplasmic material, autophagy limits cellular stress and promotes survival of long-lived memory cells [35,36]. Autophagy functions have been shown to decline with age [37,38]. Studies have shown that impairment of key autophagy genes in aged mice or by a genetic deletion system in young adult mice leads to loss of function in memory CD8 T cells and enhanced production of inflammatory cytokines including interferon (IFN)-γ, interleukin (IL)-1β, tumor necrosis factor (TNF), and IL-6 [38][39][40][41][42].…”
Section: Immune Senescencementioning
confidence: 99%
“…Autophagy functions have been shown to decline with age [37,38]. Studies have shown that impairment of key autophagy genes in aged mice or by a genetic deletion system in young adult mice leads to loss of function in memory CD8 T cells and enhanced production of inflammatory cytokines including interferon (IFN)-γ, interleukin (IL)-1β, tumor necrosis factor (TNF), and IL-6 [38][39][40][41][42]. Thus, impaired autophagy mechanisms in elderly individuals likely contribute to the inflammaging phenotype.…”
Section: Immune Senescencementioning
confidence: 99%
See 1 more Smart Citation